First experience with a fixed combination of levofloxacin and ketorolac in cataract surgery - V. P. Nikolaenko; D. F. Belov (Российский офтальмологический журнал)
Purpose. To develop an algorithm for efficient and safe application of the fixed combination of levofloxacin and ketorolac (Signicef® Plus) for the prevention of infectious complications and excessive inflammatory response after phacoemulsification (PE). Materials and methods. The studу group consisted of 449 patients (500 eyes), examined on 6th and 15th day after uncomplicated PE of senile cataract. Prevention of infection and inflammation included instillations of Signicef® Plus QID over five days and 0.1 % solution of fluorometholone (Floace Mono) QID for two weeks since the day of the operation. Primary outcome — proportion of patients with zero inflammatory response in the anterior segment, secondary outcomes — incidence of acute endophthalmitis, ocular surface condition and tolerance of the fixed combination. Results. Among the studied patients there were no cases of acute iridocyclitis or endophthalmitis. No inflammatory response on the 6th and the 15th day was reported in 98.8 and 100 % of cases respectively. The fixed combination was well tolerated without having a negative effect on the ocular surface. Conclusions. The use of Signicef® Plus for five days and Floace Mono for two weeks appears to be an effective and safe tool for preventing infectious and inflammatory complications of PE.